La traduzione latina dell’Inno ai patriarchi ad opera di Girolamo Picchioni: uno studio stilistico - Costa, Luca (Rivista Internazionale di Studi Leopardiani, 2024)
Giacomo Leopardi’s Inno ai patriarchi was translated into Latin in 1844 by Girolamo Picchioni (1792-1873), professor of Italian literature at Eton. This paper offers the first stylistic analysis of this translation. The most interesting element of the Latin text is its lexicon, which is the most fruitful way to gain insights about Leopardi’s own text.